False-positive XXY results by interphase FISH in cytogenetically normal XX individuals: two cases highlighting the necessity of additional laboratory follow-up - Qiliang Ding; Abigail L. Bronson; Kyna A. Byerly; Anna A. Essendrup; Elyse B. Mitchell; Cassandra K. Runke; Ross A. Rowsey; Nicole L. Hoppman (Molecular Cytogenetics)
Abstract Background Interphase fluorescence in situ hybridization (FISH) is commonly used for rapid aneuploidy detection in clinical settings. While FISH-based aneuploidy detection provides rapid results desirable for patient management, it usually only utilizes one probe per chromosome, which may lead to rare false-positive findings. Case presentation Here we report two interphase FISH results, which were false-positive for XXY in cytogenetically normal XX individuals. Both false-positive cases were due to hybridization of the Y chromosome centromeric probe DYZ3 to the pericentromeric region of chromosome 15. In both cases, chromosomal microarray revealed no detectable Y chromosome material, suggesting the hybridizations of the DYZ3 probe to chromosome 15 likely represent benign heterochromatic variants of no clinical significance. In one case, the DYZ3 hybridization was also identified in the phenotypically unaffected mother, further suggesting this is likely a rare variant of no clinical significance. Conclusions This report marks the first documentation of hybridization of the DYZ3 probe to another chromosome in cytogenetically normal individuals. Our report has important clinical implications, because DYZ3 is widely used by clinical laboratories for Y chromosome detection. Our findings underscore the necessity of confirming abnormal aneuploidy detection FISH results with additional laboratory methods such as chromosomal microarray analysis.